Performance Analysis of Information Technology Services in Higher Education using COBIT 2019 - Hariyanti, Eva; Nuzulita, Nania; Ranandha, Muhamad Erza; Indari, Ima Tri (Jurnal Sistem Informasi Bisnis, 2025)
Higher education institutions increasingly leverage information technology (IT) to improve their services. IT services are crucial in managing and supporting students, faculty, and staff. As IT governance evolves, measuring performance to identify potential service delivery issues becomes essential. This research adopts the COBIT 2019 framework, particularly the Deliver, Service, Support (DSS) domain, as a structured approach to assessing IT services' capability and maturity levels at a public university in Indonesia. The research methodology involves identifying measurement areas, collecting data, evaluating capability and maturity levels, validity testing, and providing recommendations. The study results show that the IT service maturity level of the university related to management practices in managed operations (DSS01), managed service requests and incidents (DSS02), and managed problems (DSS03) has reached level 3. Five activities in the IT service management have not been performed optimally: monitoring incidents and problems to improve task reliability, integrating key internal IT processes with outsourced service providers, comparing measures and plans with insurance policy requirements, evaluating physical modifications to IT sites to re-evaluate environmental risks, and including review knowledge in the service review meeting with the business customer. The validity results indicate that most of the measurement results align with the actual conditions of IT services, with an average validity score of 4.14. This study suggests specific improvements related to those five activities feasible for the university to implement to enhance its IT services.